Definición de la estrategia de posicionamiento de la marca empleador para la atracción de talento joven en una entidad financiera en Perú - Bocanegra Hopkins, Alfredo Eduardo (2024)
This consultancy aims to define an employer branding strategy for BBVA bank in its Peru franchise, with the goal of sustainably attracting profiles from the so-called ‘Generation Z’ over the coming years. This will provide a competitive advantage over other major companies in the financial sector by securing talent that adds value to the organization, resulting from an increase in applications for entry-level positions. The research seeks to identify the most attractive variables for the defined segment within the current employee value proposition offered by this organization. Through a communication plan that includes both digital channel efforts and in-person actions, the positioning of the bank will be emphasized based on these variables. Quantitative tools will be used to determine the preferred variables for this segment when considering joining an organization. Additionally, in-depth interviews with human resources experts will be conducted to validate the results and select the value proposition that best fits the ‘Generation Z’ segment. Then, the positioning strategy will be defined, detailing the channels to reach the target audience and how the success of the execution will be measured. The final deliverable will be the employer branding strategy that the company can use as a starting point, while allowing for future optimization and strengthening in later phases following the tracking of results. In an economic context with short- and medium-term uncertainties, where the financial system is being impacted by the increase in bank provisions, attracting suitable profiles and ensuring a steady flow of talent into the organization may bring different perspectives to face the challenges that this sector will encounter in the coming years.